Propuesta de un proceso de crédito para mejorar la calidad de atención al cliente del Banco de Crédito - Sede Trujillo - Yépez Flores, Manuel Diego (2016)
The present work has as general objective: To develop and to propose an offer of a credit process that will redound to benefit of the client and of the bank. The problem of investigation is the following one: of what way was an offer of a credit process improving the quality of attention to the client of the Banco of Credit - Headquarters Trujillo?; whose hypothesis is: A credit process improves in a significant way the quality of attention to the client of the Banco of Credit - Headquarters Trujillo; the variables of study are: independent Variable: Credit process; and the dependent variable: The quality of attention to the client. For this report the explanatory research design was used – cross, as well as the methods: deductive - inductive, analytical method. In the technologies of summary of information the survey was in use. Of the obtained results, we can highlight that a credit process if it gets improved significantly is going to benefit the final client in the obtaining of his credit in the minor possible time and with rates superior to the market in the Credit bank of Peru sedate Trujillo. 33.45 % of the clients is very satisfied by the characteristics of his lending, whereas 33.11 % is unsatisfied and 10.58 % is very unsatisfied. 38.23 % of the clients feels very well with the procedure of disbursement in the Credit bank of Peru sedate Trujillo, 22.87 % indicates that it is bad. One thought that a deficit of personnel exists for the evaluation and fingering of the credit processes, also that the system that one handles is obsolete, lack in communication exists between the departments of marketing and credits and an excess of work exists. These results were the base to propose actions that allow to improve the credit processes. For the exposed thing, one concluded that the offer of a credit process to improve significantly the quality of attention to the client in the Credit bank of Peru sedates Trujillo.